Efficiency of whole‐exome sequencing in old world and new world primates using human capture reagents. Issue 3 (19th April 2021) - Chan, Jeannie; Yao, Wen; Howard, Timothy D.; Hawkins, Gregory A.; Olivier, Michael; Jorgensen, Matthew J.; Cheeseman, Ian H.; Cole, Shelley A.; Cox, Laura A.
Abstract: Background: Whole‐exome sequencing (WES) can expedite research on genetic variation in non‐human primate (NHP) models of human diseases. However, NHP‐specific reagents for exome capture are not available. This study reports the use of human‐specific capture reagents in WES for olive baboons, marmosets, and vervet monkeys. Methods: Exome capture was carried out using the SureSelect Human All Exon V6 panel from Agilent Technologies, followed by high‐throughput sequencing. Capture of protein‐coding genes and detection of single nucleotide variants were evaluated. Results: Exome capture and sequencing results showed that more than 97% of old world and 93% of new world monkey protein coding genes were detected. Single nucleotide variants were detected across the genomes and missense variants were found in genes associated with human diseases. Conclusions: A cost‐effective approach based on commercial, human‐specific reagents can be used to perform WES for the discovery of genetic variants in these NHP species.